Characterization of intermetallic particles in aluminium alloy AA5083 series after recrystalization heat treatment - Peter, Octovia (2007)
The distribution and morphology of intermetallic particles' size and distribution after recrystallization heat treatment in aluminium alloy AA5083 series is characterized in this project. Formation of intermetallic particles, Al(Fe,Mn)Si and Mg2Si occurred in the matrix during solidification of original cast ingots of rolled sheets [1]. Final size and distributions of these particles in Al-Mg sheets depend on thermo-mechanical processing performed on them. The experimental procedures conducted to obtain the data including metallography, Scanning Electron Microscopy with Energy Dispersive Spectroscopy for specimen's image capture, quantitative measurement technique - Jeffries method. Characterization technique applied in this study has successfully interpreted the intermetallic particles phase distribution as either a (silicon rich) or 3 (Fe and Mn rich). The understanding obtined from this study can be best applied in the manufacturer of aluminium alloy in designing, required material properties by suitable heat treatment temperatures.